APPLYING CLASSROOM DESIGN CONCEPT TO INCREASE THE STUDENTS’ INTEREST IN LEARNING ENGLISH - Misba; Syarifuddin Tjali (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
Classroom design is one of the important components in the learning process in the school which demands high innovation and creativity during the class. On the other hand, the teacher as a supervisor in the classroom should pay more attention to the influenced factors of the students? interest. One of the influenced factors comes from classroom design or environment. In this case, the researcher found that the teachers in SMA Negeri 7 Pinrang have been improving their teaching methods but they do not concern the classroom design. The objective of this research is to know whether the classroom design influences the students? interest or not in English learning activity of SMA Negeri 7 Pinrang. In doing this research, the researcher held intensive meeting related to designing the classroom to raise the students? interest in learning English and giving a questionnaire to the students to know their response. The result of this research showed there was a positive and significant influence of classroom design to the students? interest.